Social Impact Measurement: Current Approaches and Future Directions for Social Entrepreneurship Research - Rawhouser, Hans; Cummings, Michael; Newbert, Scott L. (Entrepreneurship Theory and Practice, 2019)
Despite the importance of social impact to social entrepreneurship research, standards for measuring an organization’s social impact are underdeveloped on both theoretical and empirical grounds. We identify a sample of 71 relevant papers from leading (FT50) business journals that examine, conceptually or empirically, the measurement of social impact. We first describe the breadth of definitions, data sources, and operationalizations of social impact. Based on this analysis, we generate a typology of four approaches to conceptualizing social impact, which we use to organize insights and recommendations regarding improved measurement of the social impact of entrepreneurial ventures.